Influence of winter rations and gains on subsequent pasture gains. - Pickett, A.G.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
This test began with good to choice steer calves. The purpose is to use bluestem grass to the best advantage in producing beef. Two of the lots were fed out at the close of the first season's: grazing And the other three lots have been wintered and will be grazed a second season.
Keywords: Beef; Rations; Gain; Bluestem grass